The Mini-Mental State Examination (MMSE) as a Cognitive Screening Tool in Duchenne Muscular Dystrophy - Flávia Nardes; Alexandra Prufer de Queiroz Campos Araújo; Márcia Gonçalves Ribeiro; Maíta Bittar; Hanid Fontes Gomes (Korean Child Neurology Society, 2020)
Purpose Given that intellectual disability affects 15% to 63% of boys with Duchenne muscular dystrophy (DMD), it is relevant to evaluate if the Mini-Mental State Examination (MMSE) is a reliable test for screening in these cognitively impaired boys. Methods A descriptive study of 74 DMD boys was performed. Age, years of schooling, genotype, and performance in the MMSE and Wechsler Intelligence Scale for Children (WISC)-IV were verified. Results Sixty-seven patients, with a mean of age 12.1±3 years were enrolled. Verbal comprehension (76.9±13.9) and working memory (71.2±16.7) indexes showed the highest impairment. Correlation between the MMSE (20.3±6.1) and WISC-IV (74.4±15.6) was moderate (r=0.556). Conclusion The MMSE is a good cognitive screening test for DMD patients of 9 years and older, particularly in countries where the public health system does not provide expensive neuropsychological batteries, and has 78% accuracy and 82% sensitivity for scores ≤21. Subtests of the MMSE with better discriminatory power (for orientation, attention, and calculation) can help educators, teachers, and families to develop simple activities or academic games that enhance such mental skills.